Designer eggs with an increased content of omega-3 fatty acids and pigments - production and health benefits of their consumption - Kralik, Zlata (Array, 2021)
Designed-enriched products have been recently one of the most interesting areas of research and innovation in the animal production and food industry. These products are considered functional foods and contain ingredients that have beneficial physiological effects on human health. Designed or enriched eggs are an important type of functional food in poultry production. Demand for functional foods in the market has been increasing in recent years. Due to the increased interest of people in buying designed products, there is a production adjustment in the poultry industry. Composition change of laying hens feed affects nutritional composition change of eggs as well as their quality preservation. This process can an effect of the change in the concentration of cholesterol and its fractions, fatty acids, and pigments in eggs. It is evident from the relevant scientific literature that designer eggs consumption can have a positive effect on human health. Therefore, the aim of this paper is to describe different concepts of designer eggs production and emphasize the health benefits of their consumption in humans.